An Investigation Of The Impacts Of Warrant Issue On The Underlying Stocks - Yip, Yen Yen (2005)
This study investigates the impacts of warrant issue on the underlying stocks on the Bursa Malaysia. More specifically, the study analyses price, systematic risk (beta) and volume changes of underlying stocks surrounding first-time warrant introductions.